Study on Properties of the Blue and Yellow Offset Printing Inks - Nguyen, Thanh Tam; Tran, Anh Dung; Tran, Thi Thuy (Old Journal, 2018)
Offset printing ink has been using in security printing industry such as banknotes, cheques, passport... In this article, offset printing ink of blue and yellow properties have been characterized in order to find a simple and performance ink fomular. The comparision between blue and yellow ink has also been studied the optimal ink fomular has been applied on different materials and the offset ink industry. The stability of offset ink has been approved.